Short-horizon excess returns and exchange rate and interest rate effects - Joseph, Nathan Lael; Lambertides, Neophytos; Savva, Christos S. (My University, 2015)
We examine the effects of foreign exchange (FX) and interest rate changes on the excess returns of U.S. stocks, for short-horizons of 1–40 days. Our new evidence shows a tendency for the volatility of both excess returns and FX rate changes to be negatively related with FX rate and interest rate effects. Both the number of firms with significant FX rate and interest rate effects and the magnitude of their exposures increase with the length of the return horizon. Our finding seems inconsistent with the view that firms hedge effectively at short-return horizons.
Keywords: Bivariate GJR-GARCH-M; Exchange rate and interest rate effects; Fama-French-Carhart (FFC) factors; Smooth transition function; Time-varying conditional correlations